PELAKSANAAN PEMBELAJARAN JARAK JAUH DI SEKOLAH MENENGAH KEJURUAN - Agus Hartoyo; Septian Nur Ika Trisnawati (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
The impact of Covid-19 requires the teaching and learning system at home, so the term Distance Learning (PJJ) appears. This study aims to determine how to prepare Vocational High School's teachers in implementing PJJ. Trying to reveal data and conditions in the field about teachers' understanding of PJJ, how to implement PJJ, as well as supporting factors and obstacles during the learning process. The research method used a qualitative approach. The researchers used purposive sampling, the sample is selected according to what the researchers want, so that the sample represents the desired characteristics. The data collection instruments that be used were questionnaires and interviews. From observations and interviews, SMK Muhammadiyah Delanggu is ready to apply PJJ. This can be seen from schools that provide internet funds every month, providing computer laboratories for students who do not yet have adequate technological facilities. The school also keeps in touch with parents regarding student progress during the PJJ. Teachers who innovate and conducted IT training to improve the ability to use technology online. In addition to the readiness of facilities and services provided by schools to students, school faces challenges in implementing practical learning. The implementation of blended learning that has been applied has not been able to have a significant impact on improving student skills. With good readiness and challenges that still have to be faced, it is necessary to conduct a thorough evaluation as to whether PJJ is indeed effectively implemented at the vocational high school level.